Faktor-Faktor yang Mempengaruhi Kemiskinan di Sumatera Barat Menggunakan Metode Analisis Jalur - Deska Warita; Dewi Murni; Yenni Kurniawati (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – Poverty is a problem that until now has not been resolved by the government in Indonesia. West Sumatra is one of the provinces in Indonesia that did not escape from poverty. Formulation of the problem of this research are the factors that influence significantly poverty in West Sumatra and how much influence these factors against poverty in West Sumatra. Data were taken in 2013 in West Sumatra books in Figures 2014. This research in the form of research by using path analysis method, a method that can analyze the factors that influence directly and indirectly to poverty. Factors that affect directly poverty is unemployment and education, whereas the factors that influence indirectly poverty is education and GDP.Keywords – path analysis, poverty, factors that affect poverty.